Rationale for an international consortium to study inherited genetic susceptibility to childhood acute lymphoblastic leukemia - Sherborne, Amy; Hemminki, Kari; Kumar, Rajiv; Bartram, Claus R.; Stanulla, Martin; Schrappe, Martin; Petridou, Eleni; Semsei, Ágnes F.; Szalai, Csaba; Sinnett, Daniel; Krajinovic, Maja; Healy, Jasmine; et al. (Haematologica, the hematology journal, 2011)
Acute lymphoblastic leukemia is the major pediatric cancer in developed countries. To date most association studies of acute lymphoblastic leukemia have been based on the candidate gene approach and have evaluated a restricted number of polymorphisms. Such studies have served to highlight difficulties in conducting statistically and methodologically rigorous investigations into acute lymphoblastic leukemia risk. Recent genome-wide association studies of childhood acute lymphoblastic leukemia have provided robust evidence that common variation at four genetic loci confers a modest increase in risk. The accumulated experience to date and relative lack of success of initial efforts to identify novel acute lymphoblastic leukemia predisposition loci emphasize the need for alternative study designs and methods. The International Childhood Acute Lymphoblastic Leukaemia Genetics Consortium includes 12 research groups in Europe, Asia, the Middle East and the Americas engaged in studying the genetics of acute lymphoblastic leukemia. The initial goal of this consortium is to identify and characterize low-penetrance susceptibility variants for acute lymphoblastic leukemia through association-based analyses. Efforts to develop genome-wide association studies of acute lymphoblastic leukemia, in terms of both sample size and single nucleotide polymorphism coverage, and to increase the number of single nucleotide polymorphisms taken forward to large-scale replication should lead to the identification of additional novel risk variants for acute lymphoblastic leukemia. Ethnic differences in the risk of acute lymphoblastic leukemia are well recognized and thus in assessing the interplay between inherited and non-genetic risk factors, analyses using different population cohorts with different incidence rates are likely to be highly informative. Given that the frequency of many acute lymphoblastic leukemia subgroups is small, identifying differential effects will realistically only be possible through multi-center pooled analyses. Here, we review the rationale for identifying genetic risk variants for acute lymphoblastic leukemia and our proposed strategy for establishing the International Childhood Acute Lymphoblastic Leukaemia Genetics Consortium.